Split potassium application delays senescence and increases grain yield in winter wheat grown on sandy and silt loam soils - Wang, Yongbing; Yin, Xiaoxiao; Wang, Xin; Ali, Muhammad Fraz; Lin, Xiang; Gu, Shubo; Han, Yong; Wang, Dong (Frontiers in Plant Science, 2025)
BackgroundThe judicious application of potassium (K) fertilizer plays a critical role in increasing potassium use efficiency, leaf photosynthesis capacity, and winter wheat yield. However, there is no unified conclusion on the yield-increasing effect of split K fertilizer application. In addition, the response mechanism of winter wheat to split K application across different soil types remains unclear.AimsThe aim of this study was to investigate the mechanism underlying the effects of split K application on winter wheat yield across different soil types and to provide a basis for optimized and judicious K fertilization in the Huang-Huai-Hai plain (3HP).MethodsA two-year field experiment with winter wheat from 2016 to 2018 on silty and sandy loam, using three K application levels (K0, no K; K1, 96 kg ha-1; and K2, 120 kg ha-1) and two methods (T1, 100% basal application, and T2, 50% basal application + 50% topdressing at jointing).ResultsThe split K application increased the K and nitrogen (N) accumulation of winter wheat plants compared to a single application. It also enhanced the flag leaf SPAD value, net photosynthetic rate (Pn), superoxide dismutase (SOD) activity, catalase (CAT) activity, and soluble protein content after flowering, while decreasing the malondialdehyde (MDA) content in both soil types. Additionally, split K application improved the grain-filling rate at 25 days after flowering, prolonged the active grain-filling period (D) and the actual filling period (T3), and enhanced the 1000-grain weight, grain yield, agronomic efficiency, and partial factor productivity of K fertilizer. Moreover, in sandy loam soil, the split K application was more effective in improving the SPAD value, Pn, Plant N and K accumulation, 1000-grain weight, yield, and agronomic efficiency of K fertilizer compared to silty loam soil. ConclusionThis study provides a basis for region-specific and soil-tailored potassium fertilizer management strategies, thereby optimizing resource utilization.